Highly efficient chemoselective hydrogenation of 5-HMF to BHMF over reusable bimetallic Pd-Ir/C catalyst - Ratrey, Geetanjali; Solanki, Bhanupratap S.; Kamble, Sanjay P.; Rode, V. Chandrashekhar (ChemistrySelect, 2022)
Catalytic synergism was observed for a bimetallic Pd-Ir catalyst supported on activated carbon for chemoselective hydrogenation of 5-hydroxymetahyl furfural (5-HMF) to 2, 5-(bishydroxymethyl) furan (BHMF) with complete conversion and 97 % selectivity under very mild reaction conditions. The structural characterization like XRD, N-2 sorption, FE-SEM and TEM suggested formation of fine nanoparticles (1.95-3.08 nm) having very higher surface area, uniform distribution and mesoporous nature of the material. XPS spectra and Pyridine-IR spectroscopy revealed formation of Pd-PdO and Ir/IrO2/IrO3 interface on the catalytic surface along with strong Bronsted acidic sites which were responsible for high efficiency of catalyst at 80 degrees C, 100 psig H-2 pressure at 5-HMF/Catalyst=20 and within 2.5 h of reaction time. A plausible reaction mechanism is also elucidated based on structure activity correlation.
Keywords: 5-HMF; Carbon; Catalytic synergism; Selective hydrogenation; Valorization